Morphological and biologica[ account on the cranberry aphid, Ericaphis scammelli (Mason) (Rhynchota Aphidoidea) (Bollettino di zoologia agraria e bachicoltura, 2024)
The nearctic aphid Ericaphis scammelli (Mason) has been recently detected inPiedmont, a NW region of Italian peninsula, infesting cultivated blueberries(Vaccinium corymbosum, V. ashei and their hybrids) and cranberry (V. macrocarpon).Details and figures are given on the aphid morphology, adding shortnotes on its taxonomy, geographical distribution, host plants and biology. In theinvestigated area this aphid species is holocyclic, overwintering as eggs, laid ontwigs of its host plants as well as on leaves. Damages and control measures arealso discussed.
Keywords: Cranberry aphid; Ericaphis scammelli; Italy